2008
DOI: 10.1002/j.2050-0416.2008.tb00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasonic Waves as a Priming Technique for Accelerating and Enhancing the Germination of Barley Seed: Optimization of Method by the Taguchi Approach

Abstract: In this study the effects of different intensities and exposure time of ultrasound on barley seed have been investigated to determine the optimal conditions for accelerating germination. For optimization, the Taguchi approach was used. The germination rates and/or yield of the treated sample seed were compared with those of the untreated seed germinated under normal conditions. The seeds were treated with ultrasonic energy (input power 20-90% of 460W) and were exposed to three time periods ranging from 5 to 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 15 publications
2
70
0
5
Order By: Relevance
“…Different cultures were subjected to ultrasonic stimulation: pepper, tomatoes and cucumbers (Markov et al 1987), fodder beans (Rubtsova 1967), radish (Shimomura, 1990), corn (Hebling et al 1995), carrot (Aladjadjiyan 2002b), chickpea, wheat, pepper, and watermelon (Goussous et al 2010), ornamental trees (Aladjadjiyan 2003a(Aladjadjiyan , 2003b, barley (Yaldagard et al 2008a(Yaldagard et al , 2008b(Yaldagard et al , 2008c.…”
Section: State Of the Artmentioning
confidence: 99%
“…Different cultures were subjected to ultrasonic stimulation: pepper, tomatoes and cucumbers (Markov et al 1987), fodder beans (Rubtsova 1967), radish (Shimomura, 1990), corn (Hebling et al 1995), carrot (Aladjadjiyan 2002b), chickpea, wheat, pepper, and watermelon (Goussous et al 2010), ornamental trees (Aladjadjiyan 2003a(Aladjadjiyan , 2003b, barley (Yaldagard et al 2008a(Yaldagard et al , 2008b(Yaldagard et al , 2008c.…”
Section: State Of the Artmentioning
confidence: 99%
“…Even if the principles of HPP and its influence on microbial inactivation have been recognized since late 1800's, the first commercial installation for hPP appeared in Japan in 1990 (4,48). Although high pressure technology is currently more expensive than traditional processing technologies, the use of high pressure offers new opportunities for food industry to respond to the demand from consumers (25,26).…”
Section: High Pressure Equipmentmentioning
confidence: 99%
“…Pressure-transmitting fluids are used in the vessel to transmit pressure uniformly and instantaneously to the products sample. Most widely used fluids are water, glycol solutions, silicone oil, sodium benzoate solutions, ethanol solutions, inert gases and castor oil (48). the food products should be packaged in a flexible packaging.…”
Section: High Pressure Equipmentmentioning
confidence: 99%
“…Gupta and Hunsigi (2010) concluded that different physical seed priming treatments in peppermint (Mentha piperita) seeds were the most effective to get maximum herb yield and net return in both varieties. Yaldagard et al (2008) reported an increase in barley yield from ultrasound treatment of 6.53%. This is probably due to increased FEP as a result of ultrasound treatment of seeds.…”
Section: Field Experimentsmentioning
confidence: 99%